How I do it: Optic nerve decompression in patient with osteopetrosis - Horčičáková, Katarína; Táborská, Jana; Bubeníková, Adéla; Beneš, Vladimír (Acta neurochirurgica, 2025)
BACKGROUND: Osteopetrosis is a rare genetic disorder causing excessive skeletal density, with a predilection to affect the skull base. This commonly leads to optic canal stenosis, optic nerve compression, and atrophy and vision loss. Timely optic nerve decompression can be an effective surgical intervention to preserve vision. METHODS: Pterional approach combining both extra- and intradural optic nerve decompression was performed. Intradural optic nerve identification proved a helpful and safe way to facilitate adequate decompression while dissecting in the region of hypertrophic anterior clinoid process. CONCLUSION: Precise surgical technique and anatomical awareness are crucial for minimizing complications and aiding recovery.
Keywords: Albers-Schönbergova nemoc; dospělí; Female; Nerve Compression Syndromes; Adult; výsledek terapie; ženské pohlaví; lidé; Optic Nerve Diseases; chirurgická dekomprese; Decompression, Surgical; Neurosurgical Procedures; Treatment Outcome; Anterior clinoidectomy; neurochirurgické výkony; Decompression; Optic nerve; úžinové syndromy; Osteopetrosis; Male; nemoci zrakového nervu; nervus opticus; mužské pohlaví; Optic Nerve; Humans